The Impact of External Debt on Nigerian Economic Growth (1990 – 2009) - Gabriel, Emori Enya (Archives of Business Research, 2015)
This study examined the Impact of External Debt on Nigerian Economic Growth (1990-2009). In order to give the study a direction, two null research hypotheses were formulated to determine the effect of external debt on investment, GDP, exchange rate and inflation. The research design used for this study was the ex-post facto research design. The econometric model employed was co-integration and error correction model to evaluate the inherent relationship between external debts and economic growth in Nigeria. The result revealed that, the impact of external debt has a positive effect on the growth of Nigerian economy. And conclude that, the severity of external debt within the period is reflected in the country’s inability to meet the debt service obligations particularly scheduled debt service in relation to its foreign currency earnings. It was recommended that, the federal government should initiate the use of more superior methods to negotiate for fixed interest payment and amortization schemes.